In Vitro Evaluation of the Fracture Resistance of CAD/CAM Materials for Fixed Partial Dentures - Papala Sesha Reddy; Mallikarjun H. Doddamani; Ngangbam Johnson Singh; Ashtha Arya; K. Vijayakanth; Vignesh Veerakumar (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Computer-aided design/computer-aided manufacturing (CAD/CAM) materials have revolutionized dental restorations, offering enhanced mechanical properties and esthetic outcomes. However, the fracture resistance of various CAD/CAM materials used in fixed partial dentures (FPDs) remains a crucial determinant of their clinical success. Materials and Methods: Three CAD/CAM materials—lithium disilicate, zirconia, and resin-based composite—were selected for the study. A total of 45 three-unit FPD frameworks (15 specimens for each material) were fabricated using standardized CAD/CAM protocols. The frameworks were cemented onto artificial abutments and subjected to thermocycling to simulate oral conditions. Fracture resistance was tested using a universal testing machine, applying a load at a crosshead speed of 1 mm/min until failure occurred. The fracture loads were recorded in Newtons (N) for statistical analysis. Results: The zirconia group exhibited the highest mean fracture resistance (1,800 ± 120 N), followed by lithium disilicate (1,200 ± 100 N) and the resin-based composite (900 ± 80 N). Statistical analysis using ANOVA revealed significant differences in fracture resistance among the groups (P < 0.05). Failure modes varied, with zirconia specimens predominantly showing cohesive fractures, while lithium disilicate and the resin-based composite exhibited mixed failure patterns. Conclusion: Zirconia demonstrated superior fracture resistance compared to lithium disilicate and the resin-based composite, making it a more reliable material for FPDs in high-stress areas. Lithium disilicate remains a suitable option for esthetic regions, while the resin-based composite may be limited to low-stress applications. These findings underscore the importance of material selection based on clinical requirements to ensure long-term success of FPDs.